Performance Analysis of Synchronous Multilink in Wireless-Based Computer Networks - Dewa, Gilang Raka Rayuda (ILKOMNIKA, 2025)
The increasing demand for data transmission results in throughput degradation, which lowers the data rate and increases network outages. ITU notes that global mobile broadband surpasses 1ZB and continues to grow in successive years. Numerous techniques have been investigated to maintain the expected throughput with low computational complexity, including the synchronous multilink method. This technique generates multiple data links to enable simultaneous transmission, allowing for the transmission of more data. However, there is no unified analytical model that captures the inherent trade-offs with procedural simulation in multilink operations. Accordingly, this paper provides a comprehensive analysis of synchronous multilink. The analysis includes the work system, constraints, mathematical expression, Markov chain model, and performance result of synchronous multilink. The simulation results indicate that the synchronous multilink offers promising performance, albeit with certain limitations, for wireless-based computer networks.